1995
DOI: 10.1016/0035-9203(95)90105-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of snake bites by Bothrops species and Lachesis muta in Ecuador: laboratory screening of candidate antivenoms

Abstract: Bothrops xanthogrammus/asper, B. atrox and Lachesis muta are probably responsible for most cases of severe envenoming in Ecuador. In recent years, the most widely used antivenom ('Myn' Ronti, imported from Mexico) has proved clinically ineffective. There is an urgent need to identify an effective alternative for clinical testing. Five antivenoms with activity against Bothrops venoms were compared using standard World Health Organization rodent and in vitro assays: (i) 'Myn', Ronti Mexico SA ('B. atrox', 'Crota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 10 publications
0
16
0
3
Order By: Relevance
“…In an earlier preclinical laboratory study, the neutralising potency of five antivenoms (Brazilian, Ecuadorian, Mexican, and two Colombian) was tested against the venoms of B atrox, B asper , and B xanthogrammus 5 6. The Brazilian antivenom proved most effective, followed by the Ecuadorian and two Colombian antivenoms.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier preclinical laboratory study, the neutralising potency of five antivenoms (Brazilian, Ecuadorian, Mexican, and two Colombian) was tested against the venoms of B atrox, B asper , and B xanthogrammus 5 6. The Brazilian antivenom proved most effective, followed by the Ecuadorian and two Colombian antivenoms.…”
Section: Introductionmentioning
confidence: 99%
“…A good predictive performance was observed in potential distribution models for almost all venomous snakes, including those of medical importance such as Bothrops asper, B. atrox, B. brazili, Bothrocophias microphthalmus, Bothriopsis bilineata, B. taeniata, Lachesis muta [4,22,23], except Micrurus dumerilii.…”
Section: Discussionmentioning
confidence: 99%
“…Of these communities, 75% are located in the western region of Ecuador, 14% in the central region, and 11% in the eastern region. In the latter, our model estimates an extensive area with high snakebite risk values, [22], Theakston et al [23], Praba-Egge et al [25]) and the more comprehensive ones do not provide enough spatial details (e.g. González-Andrade and Chippaux [2]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following examples emphasize this point. Theakston et al (1995) studied 5 pAVs and 1 mAV prepared by different manufacturers and found vast differences in their neutralizing potencies against venoms of Bothrops species and Lachesis muta. Similar observations were made on 4 pAV's anti-Bothrops prepared by different manufacturers from 4 countries (Bogarin et al, 1995).…”
Section: The Number Of Poisonous Snakes In the Areamentioning
confidence: 99%